An Experimental Test of Novel Ecological Communities of Imperiled and Invasive Species. Issue 2 (26th February 2016) - Goodchild, Shawn C.; Stockwell, Craig A.
Abstract: Imperiled fish species are often managed by establishing refuge populations as a hedge against extinction, but suitable sites are often at a premium. Thus, managers may wish to consider novel strategies, such as establishing multispecies refuges that already include undesirable species. To determine the suitability of multispecies refuges, we established experimental communities that included allopatric and sympatric communities of three fish species: the endangered Pahrump Poolfish Empetrichthys latos, the Amargosa Pupfish Cyprinodon nevadensis, and the invasive Western Mosquitofish Gambusia affinis . Mosquitofish juvenile production was not significantly affected by the presence of the other species (mean ± SE: 50 ± 18 in allopatry, 33 ± 6 with poolfish, and 38 ± 7 with both poolfish and pupfish). Similarly, pupfish persisted in sympatry with both poolfish and mosquitofish, but pupfish had higher juvenile production when maintained in allopatry (557 ± 248) and in the presence of poolfish (425 ± 36) than in the presence of both poolfish and mosquitofish (242 ± 32). By contrast, poolfish juvenile production was high in allopatry (123 ± 17) but significantly lower in the presence of pupfish (6.6 ± 1.2) and mosquitofish (1.0 ± 0.5) individually and in a community of all three species (0.5 ± 0.4). This suggests that translocated pupfish can coexist in refuges containing nonnative mosquitofish but that endangered poolfish are not compatible with the other species and the current management of poolfish in single‐species refuges is appropriate. Consequently, our results indicate that multispecies refuges are suitable for some endangered species, which will give managers more latitude in the management of these species. Received March 30, 2015; accepted October 27, 2015